Simplicity, Accountability and Relationships: Three ways to ensure MEL supports Adaptive Management - and Roche, Chris (2018)
Based on a recent discussion in Manila, Chris Roche reflects on how Monitoring, Evaluation and Learning can better support 'adaptive programming'.